Additive manufacturing of polypropylene micro and nano composites through fused filament fabrication for automotive repair applications. (7th December 2022) - Jahromi, Fareed Tamaddoni; Nikzad, Mostafa; Prasad, Krishnamurthy; Norén, Johan; Isaksson, Mats; Arian, Alaleh; Sbarski, Igor
Abstract: The emerging Additive manufacturing technologies are being adopted by different industries, which require developing new materials and procedures. Here we report the development of polypropylene (PP) based composite materials for fused filament fabrication (FFF) process with the aim of enabling fully automatic robotic repair application of plastic components in automotive industry. A key challenge in repair and joining of polyolefins, which are widely used in such applications, is understanding the interplay of microstructural features and the joining mechanisms employed to achieve a uniform and fully functional repaired components. Specifically, for components manufactured from polypropylene based material, we show that the addition of ethylene propylene diene monomer (EPDM), polyisobutylene (PIB) and carbon black (CB) successfully modifies its matrix and produces a composite material ideal for additively repairing of complex geometries found in the automotive applications. This was brought about by effective reduction of the crystallinity of the composite PP matrix from 46.2% to 34.4% and resulting in a net reduction in warpage of the FFF 3D printed samples. Further, the thermal stability of the developed composite was improved with the addition of a moderate amount of carbon filler, enabling an FFF process with higher hot‐end temperatures, which subsequently allowed for tuning of the raw material's viscosity, and hence ensuring consistent deposition of molten filaments for building successive layers. Mechanical properties' analysis revealed that the addition of 10 wt.% CB increased the true stiffness (storage modulus) by 20%, the impact strength by 62%, with the drop in ultimate tensile strength of 11%. The optimal elongation at break and toughness were achieved for the samples containing 2 wt.% CB increasing these key properties by 62% and 58%, respectively. In terms of the melt flow index (MFI), as a key rheological indicator, the measured value ranged between 12.5 and 19.0  g / 10 min for all compositions suitable for the FFF process. Morphological analysis of the extruded filaments and fracture surface of impact test samples showed a mesoscale interspersion of polymer phases and a proper filler dispersion in the matrix material with sizes ranging from hundreds of nanometers to hundreds of microns. The developed 3D‐printable PP composite filament was successfully used in a robotic cell to repair broken plastic lugs of a car headlight assembly.